INFLUENCE OF THE LAURACEAE FAMILY ON THE DYNAMICS OF A MIXED OMBROPHILOUS FOREST REMNANT - Kieras, Wesllen Schuhli; Machado, Sebastião do Amaral; Pelissari, Allan Libanio; Cysneiros, Vinicius Costa; da Silva, Samuel Alves (Floresta, 2020)
Lauraceae family has one of the highest values of importance in the Mixed Ombrophilous Forest (MOF). The commercial value of some of its species was a reason for intense forest exploitation in the southern region of Brazil. Considering the hypothesis that it provides an essential subsidy for the constitution of this forest type, the aim of this study was to identify and quantify the influence of Lauraceae family in the dynamics of a 15.2 ha MOF remnant. Census data were collected every three years, since 2007, in which all trees with a circumference at 1.3 m height equal to or greater than 30 cm were identified and measured. Dynamics were analyzed by periodic increment in diameter, recruitment, and mortality through the measurement periods, while cluster multivariate analysis and canonical correlation were applied for grouping species and assessing their importance on the forest remnant dynamics. Diameter distribution prognosis of Lauraceae and its species was obtained through a transition matrix. Eleven tree species of Lauraceae family were identified, which showed decreasing diameter distribution and value of importance equals to 9.51%. Using cluster analysis, five groups were obtained, while the canonical correlation of 0.551 was considered moderate and statistically significant by Wilks’ Lambda test. By the projection of diameter distribution, it was verified that the study community is stable and self-regenerative. Although it is considered moderate, the influence of family on the forest remnant tends to increase with the advance of ecological succession.